Awareness of Janani Suraksha Yojana Among Economically Backward Section in Rural Punjab - Pandey, V.; Kaur, S. (International Journal of Bio-resource and Stress Management, 2016)
The present study was conducted in Punjab state to assess the awareness of beneficiaries about Janani Suraksha Yojana (JSY). All the three socio-cultural zones of Punjab i.e. Majha, Malwa and Doaba were selected. A total of eleven districts i.e. seven from Malwa, two from Majha and two from Doaba were selected through proportionate random sampling. From each selected district two blocks were selected throughpurposive sampling. Hence, a total of 22 blocks were selected. From each block, one village was selected randomly. A list of beneficiaries in the age group of 20–35 years was prepared with the help of anganwadi workers and ASHA workers for each selected village. Twelve mothers were selected randomly from the prepared list. Thus, 264 beneficiaries comprised the sample for this purpose. A self-structured interview schedule was prepared to collect the data from the beneficiaries. Results revealed that most of the rural mothers were in the age group between 26–30 years and 30.0% of them were educated up to middle level. Majority of the rural mothers were housewives and belonged to scheduled caste families. Rural mothers were fully aware about the specific aspects of JSY i.e. free transportation facilities and cash assistance for pregnant women. The results of the study also indicated that family income and organizational membership were significantly associated with level of awareness of the beneficiaries.